Social Responsibility Orientation of Banking in Indonesia (Case Study on Islamic Banking in North Sumatra) - Rizal, Muhammad; Ramadhan, Muhammad; ., Nurlaila; ., Kamila; Siregar , Saparuddin; Rahmadana, Muhammad Fitri (Journal of Ecohumanism, 2024)
This research investigates how Corporate Social Responsibility (CSR) orientations, attitudes, competencies, government regulations, societal pressures, environmental organizational pressures, and media pressures influence the social performance of Islamic and conventional banks in North Sumatra, in compliance with the Financial Services Authority Regulation No. 51 of 2017 on green banking and sustainable development. The study sampled 106 respondents from 5 Islamic banks, using Structural Equation Modelling (SEM) with Smart PLS 4.0. The findings reveal that CSR orientations grounded in philanthropic, legal, ethical/social, and economic responsibilities significantly impact the social performance. Attitudes not affected on Islamic banks, while competencies impact Islamic. Societal pressures influence Islamic banks, whereas government regulations not affected on Islamic banks. Environmental/social organizational pressures impact not affected on Islamic banks, and media pressures also.